2017
DOI: 10.3390/ijerph15010017
|View full text |Cite
|
Sign up to set email alerts
|

1950MHz Radio Frequency Electromagnetic Radiation Inhibits Testosterone Secretion of Mouse Leydig Cells

Abstract: More studies that are focused on the bioeffects of radio-frequency (RF) electromagnetic radiation that is generated from the communication devices, but there were few reports with confirmed results about the bioeffects of RF radiation on reproductive cells. To explore the effects of 1950 MHz RF electromagnetic radiation (EMR) on mouse Leydig (TM3) cells. TM3 cells were irradiated or sham-irradiated continuously for 24 h by the specific absorption rate (SAR) 3 W/kg radiation. At 0, 1, 2, 3, 4, and 5 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
4
14
0
1
Order By: Relevance
“…Meanwhile, CCK-8 results showed that cell viability significantly declined after 12, 36, and 48 h EMR exposure. Similar to our findings, Liu et al found that 1950 MHz EMR caused the percentage of apoptotic cells to significantly increase after 48 h [25]; our previous research results showed that 1800 MHz EMR for 1, 4, and 8 h caused a significant increase in the percentage of late apoptotic cells [24]; Lin et al found that 1950 MHz, SAR 3 W/kg EMR for 24 h can cause adverse effects on TM3 cell proliferation [26]; Bilal et al indicated that mobile phone radiation had an obvious apoptotic effect on MCF-7 cells [27]; Kesari et al claimed that 3G cell phone network exposure caused cell apoptosis in rat brain [28]; and Buttiglione et al proved that cell viability significantly decreased after 24 h of RF-EMF exposure [29]. In order to qualitatively study the cellular biological effects of cell phone radiation, this study simulated cell phone radiation at 1800 MHz, 2 W/kg.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, CCK-8 results showed that cell viability significantly declined after 12, 36, and 48 h EMR exposure. Similar to our findings, Liu et al found that 1950 MHz EMR caused the percentage of apoptotic cells to significantly increase after 48 h [25]; our previous research results showed that 1800 MHz EMR for 1, 4, and 8 h caused a significant increase in the percentage of late apoptotic cells [24]; Lin et al found that 1950 MHz, SAR 3 W/kg EMR for 24 h can cause adverse effects on TM3 cell proliferation [26]; Bilal et al indicated that mobile phone radiation had an obvious apoptotic effect on MCF-7 cells [27]; Kesari et al claimed that 3G cell phone network exposure caused cell apoptosis in rat brain [28]; and Buttiglione et al proved that cell viability significantly decreased after 24 h of RF-EMF exposure [29]. In order to qualitatively study the cellular biological effects of cell phone radiation, this study simulated cell phone radiation at 1800 MHz, 2 W/kg.…”
Section: Discussionsupporting
confidence: 91%
“…Exposure of Leydig cells (in vitro) to 1,950 MHz RF was also reported to decrease P450scc expression level without changes in StAR (Lin et al, ). However, high‐dose exposure to cell phone radiation was reported to reduce expression of StAR and testosterone concentration in the testes of mice (Zang et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Many studies show that EMR exposure can affect on the quality of semen and reduce sperm count, change sperm motility and histological structure of seminiferous tubule, finally leading to infertility in human and animal model (Al‐Bayyari, 2017; Gautam et al., 2019). Also, EMR reduces blood testosterone through oxidative stress and its effect on Leydig cells (Lin et al., 2018).…”
Section: Introductionmentioning
confidence: 99%